UPAYA PENCEGAHAN KEBAKARAN PADA PEMILIK WARUNG SEMBAKO 24 JAM DI KOTA SAMARINDA - Muhammad Sultan (JURNAL BORNEO AKCAYA, 2023)
Food stalls that operate 24 hours have the potential to become a source or victim of a fire incident. Research is needed that aims to gather information about fire prevention efforts for 24-hour shop owners. This study uses a qualitative design with a phenomenological approach. The research informants were five stall keepers in the RT 27 and RT 28 Teluk Lerong Ulu Village, Samarinda City who were selected by total sampling, and key informants namely the Heads of RT 27 and RT 28. Data collection was carried out directly in January 2023 using interview guidelines, observation, and documentation. Data and information data analysis through the coding stage which consisted of several stages, namely preparing raw data to become verbatim, condensing facts, preparing probing for data deepening, collecting similar facts, determining categorization, building concepts, and narrating them. The results of the study obtained information that the 24-hour food shop keepers considered fire to be an event that could occur at any time and cause material losses to fatalities. Most of the 24-hour food shop keepers make efforts to prevent fires, including using electric service providers who are experts and experienced in making electrical system networks, participating in firefighting training, organizing, and storing merchandise neatly, and most have provided light fire extinguishers. Therefore, it is suggested to the government through the local Fire Service to form a partnership with fire volunteers to conduct firefighting training using simple methods for owners of 24-hour food stalls and other types of businesses that have a high risk of causing a fire